Sistem Kendali dan Monitoring Garasi Menggunakan Metode Fuzzy Logic Berdasarkan Jarak dan Kecepatan User - Aida Ulfia Rochmah; Mochammad Junus; Azam Muzakhim Imammuddin (Jurnal Jaringan Telekomunikasi, 2021)
The increase in private vehicles number will also increase the number of crimes such as vehicle theft. So the owner must have a garage to increase security. However, generally security systems still use standard security. So, a system was developed to improve security and make it easier to be more effective using the ESP32 microcontroller to process the user's distance and speed values ??to control the rolling door using fuzzy logic, monitor whether or not vehicles are in the garage through a smartphone application, manage the queuing system on the smartphone application and find out the quality of the network used. Data retrieval is done by testing the hardware performance, namely the MG996R Servo Motor, ultrasonic sensor HC-SR04, Magnetic Switch MC-38, Infrared Sensor, Buzzer Module, and 1W HPL LED and the performance of smartphone application software made using Android Studio. From the test results, the speed of the servo motor with forward rotation is obtained from fuzzy logic processing to get the maximum and minimum values. A monitoring system to determine the presence or absence of a car in the garage by utilizing the color change of the view on the smartphone application. In automatic mode the smartphone application uses a queue system, where only one user can use the application, so other users cannot access the smartphone application and receive notifications. Based on the ITU-T standard, network quality testing (QOS) using wireshark software with parameters delay, packet loss and throughput gets a very good category value.